South-South Services Trade - Dihel, Nora (OECD Trade Policy Papers, 2006)
This paper contributes to the debate on the development potential of South-South trade in services. It represents the first attempt to identify key features governing the South-South dimension of services. Services trade between developing countries is predominantly regional and may reflect an increasing tendency to incorporate disciplines to liberalise services trade in regional agreements. It is estimated that cross-border South-South exports currently represent around 10 percent of world services exports. The bulk of developing countries? exports is...